2020
DOI: 10.15585/mmwr.mm6928a2
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Profiles of a Convenience Sample of Patients with COVID-19 — United States, January–April 2020

Abstract: and Prevention with either clinical or radiographic evidence of pneumonia or acute respiratory distress syndrome, without an alternative more likely diagnosis. Sixteen participating states § submitted case investigation forms containing data collected during January 19-June 3, 2020, for 199 COVID-19 patients. Among those patients, 192 (97%) reported experiencing any symptoms, six (3%) reported experiencing no symptoms, and one (<1%) had unknown symptom status. Sufficient symptom data for § States that submitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
129
2
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 5 publications
13
129
2
7
Order By: Relevance
“…Many of our IgG-positive subjects reported some symptoms consistent with COVID-19, although only fever was significantly more common in those with positive IgG results compared to those without. There is a growing body of scientific data on nonrespiratorysymptoms of SARS-CoV-2 infection [ 16 , 17 , 18 ]. An analysis of COVID-19 symptom profiles showed that gastrointestinal symptoms (diarrhea/lack of appetite), neurological symptoms (loss of smell and/or taste), as well as chills, myalgia, headache, and fatigue, were commonly reported by patients with COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of our IgG-positive subjects reported some symptoms consistent with COVID-19, although only fever was significantly more common in those with positive IgG results compared to those without. There is a growing body of scientific data on nonrespiratorysymptoms of SARS-CoV-2 infection [ 16 , 17 , 18 ]. An analysis of COVID-19 symptom profiles showed that gastrointestinal symptoms (diarrhea/lack of appetite), neurological symptoms (loss of smell and/or taste), as well as chills, myalgia, headache, and fatigue, were commonly reported by patients with COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of scientific data on nonrespiratorysymptoms of SARS-CoV-2 infection [ 16 , 17 , 18 ]. An analysis of COVID-19 symptom profiles showed that gastrointestinal symptoms (diarrhea/lack of appetite), neurological symptoms (loss of smell and/or taste), as well as chills, myalgia, headache, and fatigue, were commonly reported by patients with COVID-19 [ 16 ]. We can hypothesize that some IgG-positive subjects may have observed nonrespiratoryCOVID-19 symptoms and therefore did not report them to a physician or sanitary inspection.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent symptoms of COVID-19 are fever, cough, fatigue and diarrhea 15 . Severe illness usually happens about 1 week after the onset of symptoms 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed COVID-19 symptoms largely in line with previous studies. Cough, breathlessness and fever were present in the clinical presentation of a large proportion (11,12,18), but we must point out how cough has little discriminatory value against other primary care consults and breathlessness is a late symptom associated with more severe illness (15.1% in non-severe cases and 37.6% in severe cases). Our work concurs that feverishness (88.7%) is a dominant symptom, but diarrhea was less common in some other studies (<8.9% in [19][20][21].…”
Section: Discussionmentioning
confidence: 99%